2010
DOI: 10.1071/sr10004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of biochars on flux of N2O and CO2 from Ferrosol

Abstract: Biochars produced by slow pyrolysis of greenwaste (GW), poultry litter (PL), papermill waste (PS), and biosolids (BS) were shown to reduce N2O emissions from an acidic Ferrosol. Similar reductions were observed for the untreated GW feedstock. Soil was amended with biochar or feedstock giving application rates of 1 and 5%. Following an initial incubation, nitrogen (N) was added at 165 kg/ha as urea. Microcosms were again incubated before being brought to 100% water-filled porosity and held at this water content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
188
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 360 publications
(210 citation statements)
references
References 31 publications
20
188
1
1
Order By: Relevance
“…Although the ways to decrease nitrification N 2 O have not been well characterized, it has been shown that the decreases of soil N 2 O emissions were often accompanied by lower nitrification rates. 16 Several hypotheses have been proposed for N 2 O decreases by biochar, including: (i) biochar reduces levels of denitrification via improving soil aeration; 17 (ii) biochar increases the adsorption of NO 3 − , thus decreasing substrate availability for denitrification; 18 (iii) biochar increases soil pH therefore driving denitrification thorough to N 2 ; 18 (iv) biochar sorbs N 2 O; 19 and (v) biochar contains ethylene which could inhibit nitrification and thus the formation of NO 3 − and N 2 O. 20 More studies are needed to clarify the effect of biochar, especially when it is used as a soil amendment in agricultural production.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although the ways to decrease nitrification N 2 O have not been well characterized, it has been shown that the decreases of soil N 2 O emissions were often accompanied by lower nitrification rates. 16 Several hypotheses have been proposed for N 2 O decreases by biochar, including: (i) biochar reduces levels of denitrification via improving soil aeration; 17 (ii) biochar increases the adsorption of NO 3 − , thus decreasing substrate availability for denitrification; 18 (iii) biochar increases soil pH therefore driving denitrification thorough to N 2 ; 18 (iv) biochar sorbs N 2 O; 19 and (v) biochar contains ethylene which could inhibit nitrification and thus the formation of NO 3 − and N 2 O. 20 More studies are needed to clarify the effect of biochar, especially when it is used as a soil amendment in agricultural production.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Relative standard deviation (based on seven replicate injections) for N 2 O was <2%. For each batch of samples, a range of standards, controls and blanks were included for quality control purposes (van Zwieten et al 2010).…”
Section: Gas Analysismentioning
confidence: 99%
“…The effects of biochar use on GHG emissions have been reported in many agricultural fields, but most of these studies were conducted in aerobic incubations or upland fields amended with wood-derived biochar (Rondon et al 2006;Spokas and Reicosky 2009;Singh et al 2010;Van Zwieten et al 2010;Scheer et al 2011;Wang et al 2012). Only a few studies have been conducted in anaerobic conditions or paddy fields Liu et al 2011;Feng et al 2012;Zhang et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have been conducted in anaerobic conditions or paddy fields Liu et al 2011;Feng et al 2012;Zhang et al 2012). The results of previous studies on biochar effects on GHG emissions varied and depended on experimental conditions such as soil type, water and fertilizer management, biochar feedstock and the pyrolysis temperature for producing biochar (Singh et al 2010;Van Zwieten et al 2010;Zhang et al 2010;Liu et al 2011;Li et al 2013). To quantify GHG emissions in rice (Oryza sativa L.) production, field studies on site are suitable because the actual field condition during cultivation is repeatedly changing between aerobic and anaerobic status, and because a large part of CH 4 emissions occurs via rice plants (Inubushi et al 1989;Yu et al 1997).…”
Section: Introductionmentioning
confidence: 99%